A novel multi-component protein vaccine ECP001 containing a protein polypeptide antigen nPstS1 riching in T-cell epitopes showed good immunogenicity and protection in mice - Yu, Jinjie; Fan, Xueting; Luan, Xiuli; Wang, Ruihuan; Cao, Bin; Qian, Chengyu; Li, Guilian; Li, Machao; Zhao, Xiuqin; Liu, Haican; Wan, Kanglin; Yuan, Xiuqin (Frontiers in Immunology, 2023)
Abstract： Tuberculosis（TB） is an infectious disease that seriously affects human health. Until now, the only anti-TB vaccine approved for use is the live attenuated Mycobacterium bovis (M. bovis) vaccine — BCG vaccine, but its protective efficacy is relatively low and does not provide satisfactory protection against TB in adults. Therefore, there is an urgent need for more effective vaccines to reduce the global TB epidemic. Subunit vaccines containing multiple immunodominant antigens and adjuvants are ideal for protection against Mycobacterium tuberculosis (Mtb) infection, because they are safe, stable, immunogenic and protective, as well as can induce the production of long-lived central memory T cells, providing longer-lasting immune protection than BCG. In this study, ESAT-6, CFP-10, two antigens full-length and the T-cell epitope polypeptide antigen of PstS1, named nPstS1, were selected to form one multi-component protein antigens, named ECP001, which include two types, one is a mixed protein antigen named ECP001m, the other is a fusion expression protein antigen named ECP001f, as candidates for protein subunit vaccines. were prepared by constructing one novel subunit vaccine by mixing or fusing the three proteins and combining them with aluminum hydroxide adjuvant, and the immunogenicity and protective properties of the vaccine was evaluated in mice.The results showed that the vaccine could induce strong humoral and cellular immune responses in mice, as well as could provide comparable protective efficacy to BCG.